Materialists and altruists in a charitable donation experiment. (18th February 2019) - Fielding, David; Knowles, Stephen; Robertson, Kirsten
Abstract: This paper presents results from a laboratory experiment that draws on insights from economics on different incentives for generosity and insights from social psychology on different personality types. Firstly, we test whether the effect of an appeal to pure altruism versus an appeal to self-interest varies across subjects. We find that there is substantial variation, and this variation is strongly correlated with a subject's level of materialism. Secondly, we test whether spoken appeals and written appeals have different effects. We find no evidence for such a difference. These results have important implications for charities' fundraising strategies and for experimental design.